Julius Zarembsky: eight views on a creative person - Zagladko, Аlina (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance. Juliusz Zarembsky (1854–1885) – a brilliant pianist, teacher and composer, favorite student of F. Liszt, who received European recognition. Many years the pianist spent in Ukraine and devoted himself to the development and promotion of its musical culture, adapting folk intonations in his compositions. The extraordinary talent of the polish pianist was highly appreciated by his contemporaries, he was foretold the glory of the «second Chopin», but his early death cut off many plans. Unfortunately, the name of J. Zarembsky after his death was under the cover of oblivion for a long time. Our knowledge of it suffers from a multitude of gaps and is insufficient, and the source study base requires addition and new reflection. Thus, it became necessary to introduce some new facts from the life and creative activity of J. Zarembsky on the basis of archival sources and Kyiv periodicals, which would significantly enrich our knowledge about the personality of this outstanding pianist. Main objectives of the article, based on the materials of the stock collection of the National Archive of Zhytomyr region, Zhytomyr Regional Museum and the National Library of Ukraine named after V. I. Vernadsky, and articles of a scientific, memoir and epistolary nature, are advocates clarifying the existing and providing new multi-vector information with an emphasis on the Kyiv speeches of J. Zarembsky. The methodology. The study involved the method of historical and cultural reconstruction (to recreate unknown facts that influenced both the creative development of J. Zarembsky and the concert life of Kyiv), as well as the system, source, biographical, axiological methods. The complex use of these methods allows one to supplement the existing knowledge about J. Zarembsky, to reveal the specifics of his Kyiv concerts in the context of the development of Ukrainian and world music culture. Results and conclusions. New biography details and facts of J. Zarembsky's concert activity are introduced into scientific use in Kyiv on the basis of a study of archival materials and periodicals in Kyiv. Known throughout Europe, the pianist, a favorite student of F. Liszt, was born and spent most of the years in Zhytomyr. The belonging of this bright, creative person to the formation of the Kyiv concert tradition serves as an additional stimulus to its subsequent, versatile study of the personalities of J. Zarembsky. The article allows us to re-evaluate the historical role, to revive public interest in the name of the outstanding polish pianist and composer J. Zarembsky, who lived for a long time in Zhytomyr.